2013
DOI: 10.1167/iovs.12-11445
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Prostaglandin E1 to Treat Acute Central Retinal Artery Occlusion

Abstract: Citation: Takai Y, Tanito M, Matsuoka Y, Hara K, Ohira A. Systemic prostaglandin E1 to treat acute central retinal artery occlusion. Invest Ophthalmol Vis Sci. 2013;54:3065-3071. DOI:10.1167/iovs.12-11445 PURPOSE. To report the efficacy of systemic prostaglandin E1 (PGE1) monotherapy for treating acute central retinal artery occlusion (CRAO).METHODS. The best-corrected visual acuity (BCVA) and side effects were evaluated retrospectively in 10 consecutive eyes (nine patients; mean age, 61.3 years) with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Common treatments for CRAO are shown in Table 3. 3,[10][11][12][13][14][15][16][17][18] Ocular massage was performed because the embolus in the central retinal artery was expected to be dislodged. 3 As medical therapies, vasodilators such as nitroglycerine and anticoagulant such as heparin have been used; however, there is no evidence that these agents are effective.…”
Section: Discussionmentioning
confidence: 99%
“…Common treatments for CRAO are shown in Table 3. 3,[10][11][12][13][14][15][16][17][18] Ocular massage was performed because the embolus in the central retinal artery was expected to be dislodged. 3 As medical therapies, vasodilators such as nitroglycerine and anticoagulant such as heparin have been used; however, there is no evidence that these agents are effective.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we propose that differences in oxygen saturation resulting in differences in the distances from the arterioles may explain the alternating pattern of retinal edema in incomplete CRAO. PGE1 administered systemically can improve the visual acuity if it is administered during the acute phase, i.e., typically within 1 day after the onset of acute CRAO [ 2 , 8 ]. The visual acuity in the current case recovered after administration of systemic PGE1 2 days after onset.…”
Section: Discussionmentioning
confidence: 99%
“…1d ) showed that the hyperreflectivity coincided with the retinal opacification around the venules and the lower reflectivity coincided with the nonedematous retinal tissue around the arterioles. Based on the pattern of onset and fundus findings, we diagnosed incomplete acute CRAO OD and immediately started a venous drip injection of prostaglandin E1 (PGE1) [ 2 ]. Fluorescein angiography performed after the initial PGE1 drip showed an arm-to-retina circulatory time of 28 s and an early-phase filling defect in the small capillary networks in the macular region (fig.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E1 (PGE1) is known to dilate blood vessels and inhibit platelet aggregation to increase blood flow 20 21. In previous reports, CRAO eyes showed better visual outcomes after PGE1 treatment (using a dosage of 80 µg/day) than that before PGE1 treatment,22 23 suggesting that PGE1 treatment is an option for treatment of CRAO. However, fatal side effects, such as cerebral haemorrhage, have been reported with high-dose PGE1 therapy 24…”
Section: Introductionmentioning
confidence: 99%